2022
DOI: 10.21037/tau-21-1161
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of long non-coding RNAs in neurogenic bladder of spinal cord injured rats: a transcriptomic analysis

Abstract: Background: Growing evidence has indicated that long non-coding RNAs (lncRNAs) are important regulators of pathological and physiological processes through various mechanisms. However, the signature of lncRNA expression and the possible roles of lncRNAs in spinal cord injury (SCI) rat neurogenic bladder (NB) have not been comprehensively explored. In this study, the expression profiles of lncRNAs and mRNAs were explored in the bladder tissue of SCI rats using next-generation sequencing (NGS).Methods: Twenty fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…In addition, Pgam1, the host gene of circRNA0722, interacted with TGF and mediated inflammation, apoptosis, and collagen accumulation, further contributing to fibrosis progression ( Wu et al, 2021 ). However, we have previously reported that NB and bladder fibrosis after SSCI is associated with the TGF- β pathway and EMT ( Ruan et al, 2022 ). Our present sequencing data showed upregulation of circRNA2378 and circRNA0722, suggesting they contribute to bladder fibrosis after SSCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Pgam1, the host gene of circRNA0722, interacted with TGF and mediated inflammation, apoptosis, and collagen accumulation, further contributing to fibrosis progression ( Wu et al, 2021 ). However, we have previously reported that NB and bladder fibrosis after SSCI is associated with the TGF- β pathway and EMT ( Ruan et al, 2022 ). Our present sequencing data showed upregulation of circRNA2378 and circRNA0722, suggesting they contribute to bladder fibrosis after SSCI.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that lncRNAs could play a role in regulating NB following SSCI and bladder fibrosis. Our previous studies showed that some lncRNAs might affect the bladder fibrosis process following SSCI through certain signaling pathways ( Ruan et al, 2022 ). For instance, in bladder fibrosis following SSCI, the lncRNA Mir155hg targets miR-155 and activates the fibrotic signaling pathway downstream, including the TGF- β 1 pathways.…”
Section: Discussionmentioning
confidence: 99%